مناسبات جریان‌های شیعی عمان با حکومت و سایر مسلمانان - بیک زاده علیشاه, مجید; نواب, سیدابوالحسن; محمدی مظفر, محمد حسن (پژوهشنامه مذاهب اسلامی, 2024)
شیعیان عمان کلیتی واحد نیستند؛ برخی بلوچ، برخی خوجه، برخی بحرینی و شماری نیز عرب عمانی هستند. در هر کدام از این گروه‌ها شخصیت، هویت و تفکر جمعی خاصی ‌مشاهده می‌شود که همین امر سطوح متفاوتی از ادغام در جامعه میزبان را برای آنها رقم زده است؛ به این معنا که هرگونه تلاشی برای تقریب و نزدیک‌کردن مناسبات شیعیان عمان با دیگر مذاهب در گام اول مستلزم بر تمرکز خود شیعیان برای حذف مانع و چالش‌های موجود بین آنهاست. محدودیت‌های قانونی و ساختاری و استفاده حکومت از آنها برای مقابله با تحرکات و فعالیت‌های جدید، چالشی دیگر در این‌باره است. افزون بر آن هرگونه تلاش برای ساماندهی شیعیان عمان، ممکن است حساسیت حکومت عمان را برانگیزد که روابط حسنه‌ای با جمهوری اسلامی دارد. این پژوهش با استفاده از دو روش مطالعۀ کتابخانه‌ای و مصاحبه با یکی از کارشناسان ارشد مسائل عمان، به بررسی بیشتر جوانب حضور شیعیان در جامعه عمان می‌پردازد و رابطه آنها را با اباضیه بررسی می‌کند که بیشتر جامعه عمان را تشکیل می‌دهند، نظام حکومتی عمان را در اختیار دارند و اشتراک‌های بسیاری نیز با شیعیان دارند. این نوشتار اباضیه عمان را گزینه مناسب تقریب و دارای قابلیت‌های لازم برای دیپلماسی فرهنگی جمهوری اسلامی در نظر می‌گیرد.
Keywords: Chiisme -- Oman; Tolérance religieuse -- Oman

Religious-Ethnic Structure of the Sultanate of Oman - Abzhapparova, Bibikhadisha (Kazakhstan Oriental Studies, 2024)
The Sultanate of Oman is a unique state of the Persian Gulf, its population lives in a rapidly developing and prosperous society. The novelty of the article consist  in the fact that it studied  the way of life, traditions, religions and the history of settlement of various ethnic groups in the life of the Sultanate of Oman, as well as the peculiarities of local languages in the country. The article examines the lifestyle, traditions, religions of various ethnic groups rooted in the life of this country, as well as the history of their arrival and settlement in Oman. The sites of settlement of large ethnic groups such as Balochis, Bahais, Luati, Zanzibari and Indians were studied, and how they assimilated into society. The article analyzes how some historical events and historical aspects of the Sultanate of Oman influenced the ethnic structure in it. The practical significance of the article lies in the fact that it will help researchers dealing with the countries of the Persian Gulf, Oriental studies and international relations. The article examines the variants of the origin of the word "Oman", the explanations left by the researchers. It was discussed which religions the people of Oman profess, which religion is more widespread in which region. We analyzed the history, lifestyle, and characteristics of the tribes and ethnic groups known in this country, where they mainly live. Attention was drawn to the country's special support for religious tolerance and peace in society.  In the methodology of writing the article, methods of analysis-synthesis, deduction, formalization, open electronic sources, works of foreign and domestic scientists who studied this topic were used.
Keywords: Tolérance religieuse -- Oman

Tolerance as a Legitimation Strategy in Oman’s Political Discourse: From Religious to Foreign Policy Principle - Daga, Giulia (The International Spectator, 2024)
In the past few decades, the concept of tolerance has gained a central place in Oman’s political discourse and foreign policy. It is often attributed to the country’s national identity, which in turn is interpreted as deriving from Oman’s Ibadi tradition, the cosmopolitan character of its maritime history and its strategic geographic location. Despite greater attention being paid to the constructive nature of Oman’s identity, including its connection with Ibadism, however, a careful reflection on how the concept of tolerance developed from a religious to a foreign policy principle is still missing. A Discourse-Historical analysis of speeches directed towards a domestic and international audience highlights how the political discourse on tolerance, by reinforcing identity-engineering efforts, supported the Omani government’s legitimation and status-seeking purposes at home and abroad.
Keywords: Tolérance religieuse -- Oman

The Omani Experience of Multi-religious Coexistence and Dialogue: A Historical Approach to the Omani Principles and its Luminous Examples - Maawali, Al Muatasim Said Saif al- (Journal of Islamic Thought and Civilization, 2021)
In a world that is increasingly hostile towards religious minorities, this paper tries to set a modern-day, successful example of multi-religious coexistence and interfaith dialogue. The paper examines historical examples derived from Omani history and explores Omani characteristics by surveying Western reports written by missionaries, visitors, and travellers of different religions in Oman. This is meant to demonstrate the hypothesis that the multi-religious coexistence and interfaith dialogue enjoyed today by the nearly fourmillion Omani population is a natural result of a long history of commitment to ‘Omani values’ and principles, practised by Oman’s Ibāḍī population with their fellow nonMuslims. The paper concludes that there is a strong correlation between the ‘Omani values’ recorded by the Western writers and the ongoing deeply rooted Omani experience of peaceful religious coexistence and interfaith dialogue. These ‘Omani values’ include the principles of tolerance, social justice, mutual respect, friendliness, hospitality, and simplicity. Finally, owing to the increasingly rising tensions between adherents of different religions, the paper recommends that such successful Omani experiences should be exported to other countries in the Muslim world and elsewhere.
Keywords: Tolérance religieuse -- Oman

Günümüz Umman İbadi̇li̇ği̇nde Di̇ni̇ Tolerans Söylemi̇ - Bahadir, Lknur (Istanbul Üniversitesi, 2021)
The discourse of religious tolerance produced at the state level as a part of this incentive has been adopted by researchers working in the field and has become the main slogan that constitutes the content of activities promoting Oman at many levels today. This study, which examines the conditions for the formation of the religious tolerance discourse adopted by Oman and its current counterpart, consists of three parts. In the first part, the historical transformation of the imamate institution, which has an important place in the sectarianization process of Ibadi and which has created its existence as an independent structure from other sects, is emphasized. In the second part, the transformation of the struggle between imamate and sultanate into a power struggle as well as religious motivations and the capacity of the movements that took place outside the country to affect this struggle and its consequences are mentioned. In the third part, the discourse of religious tolerance, which was put into circulation with the beginning of the Sultan Qaboos period, and the concrete results of this discourse were evaluated.
Keywords: Tolérance religieuse -- Oman

‏جهود سماحة الشيخ أحمد بن حمد الخليلي المفتي العام لسلطنة عمان في التقريب بين المذاهب الإسلامية - عبد اللطيف, أحمد عبد المنعم (مكتبة الجيل الواعد, 2023)
Keywords: Tolérance religieuse -- Oman

Thoughts on the stringency of the vision of tolerance within Ibadi Oman (Formation and development of the narrative of tolerance in the Ibāḍiyya in Oman since the Nahda period) - Weber, Gregor (4th Summer School on Ibadi Studies "Assessing the Study of Early Ibadi Sources: methodologies, developments and perspectives", 2022)
Keywords: Tolérance religieuse -- Oman

Potentials and limits of the Omani approach to "Religious Tolerance" in the transcultural sphere, using the example of Sheikh Aḥmad al-Khalīlī - Weber, Gregor (12th International Conference on Ibadi Studies: Far Beyond the Atlantic: Literary Production, Exchange, and Material Culture Across Brazilian and Ibadi-Omani History, 2023)
Keywords: Tolérance religieuse -- Oman

دور كلية العلوم الشرعية في نشر ثقافة الوسطية والتعايش السلمي – دراسة ميدانية على عينة من طلبة وطالبات كلية العلوم الشرعية – سلطنة عمان - جودة, أحمد حسين; السيابي, حاتم بن رشيد (المؤتمر الدولي الثاني: قضايا المجتمع المعاصرة في ميزان الشرع مقارنات وحلول, 2023)
Keywords: Tolérance religieuse -- Oman

Décryptage. À Oman, une tolérance de façade (Courrier international, 2022)
Les femmes, les homosexuels et les athées sont dans le collimateur des autorités et du grand mufti, qui prêchent uniquement la modération intermusulmane, entre ibadites et sunnites, explique ce mensuel spécialisé sur les questions de citoyenneté et de libertés dans le Golfe et le monde arabe.
Keywords: Tolérance religieuse -- Oman

الواجهة الدينية لعمان.. السلام الطائفي وإرهاب السلطة على لسان المفتي (مواطن, 2022)
تحتل عمان المرتبة الأولى بين دول الخليج في تمثيل الأقليات، حسب مؤشر المشاركة السياسية في الخليج الصادر عن مركز البيت
Keywords: Tolérance religieuse -- Oman

The declaration of His Majesty Sultan Qaboos : Towards a Harmonous Human Community - Zdanowski, Jerzy; Ziaka, Angeliki (Georg Olms Verlag, 2022)
Keywords: Tolérance religieuse -- Oman

Multiculturalism and Religious tolerance in Oman - Hajri, Hilal al- (Giornata di studio su Storia e Cultura dell’Oman, 2021)
Keywords: Tolérance religieuse -- Oman